The basic model of Islamic psychospiritual treatment based on understanding and appreciating the concept of destiny (Al-Taqdir) - Rahman, Syed Mohammad Hilmi Syed Abdul (Journal for the study of religions and ideologies, 2023)
The severity of mental and emotional disturbances is not only a topic of discussion among academics and medical practitioners, but also debated by world leaders. Despite various methods being employed to address this issue, the number of mental illness cases continues to rise each year. Therefore, it is crucial to explore alternative treatments. This article proposes a basic model of psycho-spiritual treatment that draws on an understanding and realization of Allah's taqdir, driven by faith in al-Qada' and al-Qadr, to help treat mental disorders. The proposed model takes into account that a stable and positive faith, morals, and self-identity can be formed through an understanding and realization of Allah's taqdir. This model also acts as a fundamental concept of mental and spiritual support needs by fostering a sense of dependence, hopefulness, justice, and solidarity. As such, it offers an alternative approach to psycho-spiritual treatment.